Historical Perspectives to Postglacial Uplift. Case Studies from the Lower Satakunta Region - Pohjola Jari; Turunen Jari; Lipping Tarmo; Sivula Anna; Marila Marko (Springer, 2022)
This Brief discusses a unique mechanism to combine historical and archaeological evidence with statistical geodynamic modeling to study the historical development of the Eura region in lower Satakunta, Finland; this region is known for its rich cultural history.
The book presents methods to model postglacial land uplift and the historical landscape. By using coupled data, it is possible to narrow the dating estimates of the archaeologically important places and structures and to build a more detailed reconstruction of landscape evolution in connection with the knowledge about human settlements and their movements. The resulting geospatial and uplift models are included as supplements.
The primary audience for this book is experts and professionals working in the fields of archaeology, geography, geology and geospatial data analysis.